Analysis of financing investment activities sources of textile enterprises - Khidirov, N.G. («Академик Е.А. Бөкетов атындағы Карағанды университеті» КЕАҚ баспасы, 2020)
The article analyzes the sources of financing investment activities of textile companies. The practice of financing investment projects of textile enterprises using their funds, bank loans and foreign investments was studied. The process of financing investment activity at industrial enterprises and methods for assessing the effectiveness of investment projects are investigated.
Keywords: industry; textile enterprises; investment activity; investment financing; investment strategy; sources of financing; equity; bank loans; foreign investments